Synthesis of trans-pinocarveol from oxidation of β-pinene using multifunctional heterogeneous catalysts (2023)
In this contribution, several multifunctional heterogeneous catalysts comprising an acid and a metal function were synthesized by wetness impregnation and tested in the allylic oxidation (with hydrogen peroxide as an oxidizing agent) of β-pinene, a monoterpene which is present in several plants being one of the main constituents of the turpentine oil. Among the tested catalysts, the material containing Pd with a heteropolyacid supported on SBA-15 (Pd/HPA-300/SBA-15) was the best catalyst achieving the most promising results (up to 65% of yield to trans-pinocarveol). Independent on the Pd loading (0.5 wt% or 1.0 wt%) and calcination temperature of the heteropolyacid supported on SBA-15 (200◦C-300◦C), selectivity to trans-pinocarveol remained the same. At the same time the calcination temperature affected conversion, Pd dispersion, acidity, and the surface area. When the support changed to amorphous SiO2 (with a lower surface area < 200 m2 /g) both selectivity and conversion decreased dramatically to values lower than 20%. Weak Brønsted acid sited together with a typical particles shape favors formation and selectivity to the desired product. Laboratory scaling up of β-pinene oxidation was performed (up to 10 mL) achieving the same results in terms of activity and selectivity thereby showing a possibility of a practical implementation of the proposed catalytic system. Kinetic modelling of the reaction was performed to elucidate the determining steps involving in the allylic oxidation of β-pinene. The catalysts showed to be robust since it can be used up to 3 times without apparent changes in both selectivity and conversion but with a slight presence of lixiviation.